Dual Catalyst Model Describing the Effect of Branching on the Molecular Architecture of Polyolefins. Issue 2 (17th September 2015) - Konstantinov, Ivan; Villa, Carlos; Karjala, Thomas; Jain, Pradeep
Abstract : Analytical solutions for the impact of branching on the polymer molecular architecture in the presence of two catalysts are developed. One catalyst forms only linear chains while the other produces linear as well as branched species. Emphasis is placed on the average molecular weight and polydispersity index of the populations associated with each catalyst rather than the overall quantities. By defining the cross‐incorporation number, x, which represents the relative value of the β‐hydride elimination and terminal double bond polymerization rate coefficients of each catalyst, we map the effect of branching on the molecular architecture of the polymer in order to understand the underlying kinetics and guide system design. Abstract : Analytical solutions for a system with two catalysts, one ( L ) producing only linear chains and the other ( B ) capable of long‐chain branching, are developed. The polydispersity index associated with Catalyst B displays complex behavior as a function of the number of branches per chain formed and the length of the chains produced at Catalyst L .